(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Ensuring a stable, hygienic, as well as nutritious food supplies for the poor and undernourished people of emerging economies is a serious concern today. Scarcity, high cost, and intermittent supply of healthy food have led to the hunt for an inexpensive or alternative source of excellent and nutritious food in relatively underdeveloped countries. Underutilized edible wild plants like Canavalia, Mucuna, Rhynchosia, Afzelia, Brachystegia, and Detarium, for instance, have been examined as well as proved to have high nutritional content. The number of plant species are healthy, and some have medicinal properties, as per existing studies. The usage of underutilized wild edible plants helps to combat hunger also improves rural health of the public. This study also looked at how underused wild edible plants may be exploited commercially as a source of nutritional supplements, novel food compositions, bio fortification, and product design.